Expedient Route to Access C8-Carbonylated Quinolines via Photo-Induced C(sp3)–H Oxidation - Mandal, Santu; Bera, Saikat; Debnath, Bijoy; Paul, Pallabi; Punniyamurthy, Tharmalingam (Synthesis, 2025)
Visible light-enabled C(sp3)–H oxidation of 8-alkylquinolines has been accomplished utilizing [Mes-Acr-Me]BF4 under air. The reaction offers an effective synthetic approach to direct access of C8-carbonyl quinolines bearing aldehydes, ketones, and esters groups and allows other important functional handles through postsynthetic modification. The site-selective C(sp3)–H oxidation, use of air as oxidant, substrate scope, and postsynthetic potential are the salient practical features.
Keywords: Quinoline modification; Photo-catalysis; C(sp3)–H oxidation; Organo-photocatalyst; Metal-free approach